Tunable plasmons in regular planar arrays of graphene nanoribbons with armchair and zigzag-shaped edges - Cristian Vacacela Gomez; Michele Pisarra; Mario Gravina; Antonello Sindona (Beilstein Journal of Nanotechnology, 2017)
Recent experimental evidence for and the theoretical confirmation of tunable edge plasmons and surface plasmons in graphene nanoribbons have opened up new opportunities to scrutinize the main geometric and conformation factors, which can be used to modulate these collective modes in the infrared-to-terahertz frequency band. Here, we show how the extrinsic plasmon structure of regular planar arrays of graphene nanoribbons, with perfectly symmetric edges, is influenced by the width, chirality and unit-cell length of each ribbon, as well as the in-plane vacuum distance between two contiguous ribbons. Our predictions, based on time-dependent density functional theory, in the random phase approximation, are expected to be of immediate help for measurements of plasmonic features in nanoscale architectures of nanoribbon devices.